STUDY THE INHIBITORY EFFECT OF OMPERAZOLE ON EFFLUX PUMPS FOR CIPROFLOXACINE AND NORFLOXACINE ON SOME BACTERIAL ISOLATE FROM PATIENT - AbdulRazzaq , Raghed Abd-Alatif (Diyala Agricultural Sciences Journal, 2010)
The inhibitory effect of omperazole on drug efflux pumps for decrease of antibiotic resistance in some isolates included(E.coli, Enterobacter, Staphylococcus aureus., Pseudomonas aeruginosa) to ciprofloxacin and norfloxacne.The minimal inhibitory concentration(MIC) of ciprofloxacin and norfloxacin were determined by using tow fold dilution method on muller hinton agar. The MIC of ciprofloxacine was 256µg/ml,64µg/ml, In E.coli and Enterobacter respectively and 512µg/ml in S.aureus and Ps. aeruginosa. the MIC values of norfloxacin was 512µg/ml in E.coli and Ps.aeruiginosa and 1024µg/ml in S. aureus and 256µg/ml in Enterobacter . On the other hand the MIC of omperazole alone was tested there was no effect on pathogenic bacteria. The MIC of ciprofloxacin and norfloxacion were determined after added of 100mg/ml of omperazol on each of concentration .the MIC of ciprofloxacin became 32µg/ml in E.coli and Enterobacter and 128µg/ml,64µg/ml for S.aureus and Ps.aeruginosa. while the MIC of norfloxacin after added omperazole was 128µg/ml to E.coli , 64µg/ml to Enterobacter and 256µg/ml for S.aureus and Ps.aeruginosa